Associations between physical and psychosocial work environment factors and sickness absence incidence depend on the lengths of the sickness absence episodes: a prospective study of 27 678 Danish employees. (9th September 2020) - Thorsen, Sannie Vester; Flyvholm, Mari-Ann; Pedersen, Jacob; Bültmann, Ute; Andersen, Lars L; Bjorner, Jakob Bue
Abstract : Objectives: This study examined if the association between work environment factors and sickness absence (SA) depended on the inclusion or exclusion of short-term SA episodes. Methods: We linked the 'Work Environment and Health in Denmark' survey with the 'Danish Register of Work Absences' (n=27 678). Using covariate adjusted Cox regression, we examined the associations between work environment factors and SA by changing the cut-off points for the length of the SA episodes, for example, episodes ≥1 day, ≥6 days and ≥21 days. We examined three physical work environment factors: 'Back bend or twisted', 'Lifting or carrying', 'Wet hands' and three psychosocial work environment factors: 'Poor influence', 'Role conflicts' and 'Bullying'. Results: 'Back bend or twisted' and 'Lifting or carrying' had small significant HRs for SA episodes ≥1 day and large and highly significant HRs for SA episodes ≥6 days and ≥21 days. 'Wet hands' had small significant HRs for SA episodes ≥1 day for both sexes and large and highly significant HR for ≥6 days for women. HRs of all three psychosocial factors were highly significant for SA episodes ≥1 day and ≥6 days for both sexes, and 'Poor influence' and 'Role conflicts' were significant for SA episodes ≥21 days for women. Conclusions: The physical work factors had higher associations with SA when SA episodes of 1–5 days were excluded and focus was on SA episodes ≥6 days. The psychosocial work factors were strongly associated with SA both with and without SA episodes of 1–5 days included in the analyses.